2023
DOI: 10.3389/fendo.2023.1241307
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular function in patients with type 2 diabetes mellitus by non-invasive myocardial work

Wenjia Cao,
Yan Deng,
Linyi Lv
et al.

Abstract: BackgroundDiabetes mellitus (DM) is a chronic disease that poses a serious risk of cardiovascular diseases. Therefore, early detection of impaired cardiac function with non-invasive myocardial imaging is critical for improving the prognosis of patients with DM.PurposeThis study aimed to assess the left ventricular (LV) function in patients with type 2 diabetes mellitus (T2DM) by non-invasive myocardial work technique.Materials and methodsIn all, 67 patients with T2DM and 28 healthy controls were included and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Cao et al [56] bring an element of novelty in their study that explored the LV function in patients with type 2 DM by the MW technique. They found that peak strain dispersion (PSD), a parameter assessed by 2D speckle tracking echocardiography that reflects the heterogeneity of contraction between LV myocardial segments, was positively correlated with GWW and negatively correlated with GWE.…”
Section: Clinical Valuementioning
confidence: 99%
“…Cao et al [56] bring an element of novelty in their study that explored the LV function in patients with type 2 DM by the MW technique. They found that peak strain dispersion (PSD), a parameter assessed by 2D speckle tracking echocardiography that reflects the heterogeneity of contraction between LV myocardial segments, was positively correlated with GWW and negatively correlated with GWE.…”
Section: Clinical Valuementioning
confidence: 99%